Clinical Charecterstics and Out Come of Patients with Symptomatic Corona Virus Disease 2019 in Small District of Himachal Pradesh in India - Subhash Chander; Anurag Thakur; Anil Verma; Nitin Tangri; Rakesh Chauhan (Asian Journal of Medical Research, 2020)
Background: In India Covid 19 cases started rising after the Lockdown and from January 30 to August 02 there have been 18,07,222 confirmed cases of Covid 19 with 38176 deaths. Now Covid 19 cases are present in small towns and villages as people from major cities has been migrates to their native places. This study describes the demographic, baseline comorbidity, presenting clinical complaints and outcome of the first sequentially patients with COVID -19 in a small district from Himachal Pradesh, In India. Subjects and Methods: This retrospective observational study was conducted in Dr. Radha Krishnan Government medical college, Hamirpur, Himachal Pradesh, India. The inclusion criteria for the study was All symptomatic patients with laboratory-confirmed COVID-19 by Real time polymerase chain reaction (RT-PCR) in Distt. Hamirpur in Himachal Pradesh from March 2020 to 31 July 2020. Oral consent was obtained for the study. The medical records of patients were analysed by the research team of the department of medicine, Dr. Radha Krishnan Government Medical College Hamirpur. Results: Maximum number of patients (92%) migrated from outside the state and majority from the cities of high number of Covid cases. During hospital periods 36% patients had peripheral capillary spo2 less than 95% and required oxygen support. 2(4%) patients died in the hospital and 5(10%) was referred to higher centre. 43(86%) patents recovered and discharged in stable condition. Fever (64%) was the most common symptom followed by cough (60%), fatigue (40), rhinorrhoea (28%), headache (26%) and hypogeusia (16%). Conclusion : The clinical presentation was milder and complications were seen in very few. Special attention is required to the geriatric population and with severe comorbid condition, as they are more likely to have a poor outcome.